Comparing cognitive emotion regulation, stress, depression, anxiety, and stress related to life events in people with and without periodontal disease - Ebrahim Akbari; Ali Mashhadi; Zeinab Azimi; Raheleh Abbas Nazhad; Ahamd Amiri Pichakolaei (Tehran University of Medical Sciences, 2018)
Background and Aims: While there are a lot of information about an illness risk factors, there are still some gaps in understanding factors influencing the progression of disease. Given the important role of psychological factors in physical conditions, the purpose of this study was to compare the cognitive emotion regulation, stress, depression, anxiety, and stress related to life events in people with and without periodontal disease. Materials and Methods: The type of this study was causal comparative. Research society was all clients referred to dental clinics in Lamerd and Mehr cities, then 50 people with and 50 people without periodontal disease (male and female, 15-49 years old) were selected using purposive sampling. The group without periodontal disease was matched with patient group in terms of demographic characteristics. Both groups completed cognitive emotion regulation questionnaire (CERQ), Depression Anxiety Stress Scale (DASS), and life events questionnaire. Data analysis was conducted with SPSS version 17 using multivariate analysis of variance (MANOVA). Resultes: Data analysis showed that people with periodontal disease had more stress, depression, anxiety, and stress related to life events than matched control group. The groups had significant differences in the components of self-blame, rumination, positive attention to evaluation and catastrophizing (P<0.05). People with periodontal disease had higher scores in self-blame, rumination and catastrophizing and lower scores in positive attention to evaluating compared with matched control group. Conclusion: The results showed people who were vulnerable to stressfull situations, depression, and anxiety during their lives, and also use maladaptive emotion regulation strategies, were more susceptible to periodontal disease.